2010
DOI: 10.1254/jphs.09342fp
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Calmodulin With the Multiple Binding Sites of Cav1.2 Ca2+ Channels

Abstract: Abstract. Although calmodulin binding to various sites of the Cav1.2 Ca 2+ channel has been reported, the mechanism of the interaction is not fully understood. In this study we examined calmodulin binding to fragment channel peptides using a semi-quantitative pull-down assay. Calmodulin bound to the peptides with decreasing affinity order: IQ > preIQ > I-II loop > N-terminal peptide. A peptide containing both preIQ and IQ regions (Leu 1599 -Leu 1668 ) bound with approximately 2 mol of calmodulin per peptide. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
42
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 29 publications
12
42
0
Order By: Relevance
“…Thus, it is proposed that CS L may compete with CaM for binding with Cav1.2 as a partial agonist [8], and this kind of competitive binding of CaM and CS L was eventually confirmed on the IQ motif [8]. , in IQ motif, significantly affect the CaM binding to the preIQ and IQ peptides, respectively [12]. Similarly, in present study, we found that the amounts of CS L binding with the mutants of above a.a. residues were dramatically decreased, suggesting that those amino acids are also important for the CS L binding.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Thus, it is proposed that CS L may compete with CaM for binding with Cav1.2 as a partial agonist [8], and this kind of competitive binding of CaM and CS L was eventually confirmed on the IQ motif [8]. , in IQ motif, significantly affect the CaM binding to the preIQ and IQ peptides, respectively [12]. Similarly, in present study, we found that the amounts of CS L binding with the mutants of above a.a. residues were dramatically decreased, suggesting that those amino acids are also important for the CS L binding.…”
Section: Discussionsupporting
confidence: 79%
“…A previous study [12] examined the effect of the I/E mutation on the IQ region binding to CaM. Those results indicated that the mutation nearly completely abolished CaM binding and confirmed that I1653 in the IQ region interacted with CaM, and that multiple mutations (E/K-I/D-LL/RR) decreased the affinity of the CaM-PreIQ interaction, supporting the hypothesis that these a.a. residues are important for the binding [12].…”
Section: Binding Of Cs L With Mutant Iq and Mutant Preiq Peptidessupporting
confidence: 53%
See 2 more Smart Citations
“…38 It was the words of David Yue: 'one bad apple spoils the pie'. Thereafter, crystallographic and biochemical studies revealed that CaM could at least bind at 2 other sites including the C-terminal domain of Cav1.2 channels 39,40 and the N-terminal region called NSCaTE. 41 Thus, the gap of knowledge between functional counting of CaM and these latter results is still unresolved.…”
Section: Reflections By Tuck Wah Soong Singaporementioning
confidence: 99%